Size and volume effects on the strength of microscale lead-free solder joints - Yin, L.; Zhang, X.; Lu, Chungsheng (Springer, 2009)
The fracture behavior of microscale lead-free Sn-3.0Ag-0.5Cu solder joints of different sizes was investigated under quasistatic microtension loading. The experimental results show that the ultimate tensile strength of a joint does not always increase with decreasing thickness-to-diameter ratio (d/t), which is commonly regarded as the dominant factor for mechanical constraint in the joint. A clear joint volume effect on the strength has been found, i.e., the joint's strength increases with decreasing joint volume and the correlation follows an inverse proportional function reasonably well.